2014
DOI: 10.3177/jnsv.60.94
|View full text |Cite
|
Sign up to set email alerts
|

Bindings of ChREBP and SREBP1, and Histone Acetylation around the Rat Liver Fatty Acid Synthase Gene Are Associated with Induction of the Gene during the Suckling-Weaning Transition

Abstract: Summary It has been reported that the enzymic activity of fatty acid synthase (Fas) in rat liver increases during suckling-weaning transition. In this study, we investigated whether induction of the gene (Fasn) in the rat liver during the suckling-weaning transition is regulated by histone acetylation, and the nuclear transcription factors carbohydrate response element-binding protein (ChREBP) and sterol regulatory element-binding protein 1 (SREBP1). We observed that levels of Fas and Fasn increased during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Most importantly, the strong enhancement of SREBP1 und PPRAG protein expression in the SLC-KO mice occurred in the pericentral zone which is in line with published data from mice fed with a high fat diet ( Inoue et al, 2005 ; Liu, 2012 ). For SREBP1 it was shown that this protein has binding sites at -7000 bp and -500 bp of the Fasn gene ( Amemiya-Kudo et al, 2002 ; Morishita et al, 2014 ). Furthermore it was also shown that overexpression of SREBP1c, an isoform of SREBP1, lead to significant upregulation of Fasn gene expression in hepatocytes ( Dentin et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the strong enhancement of SREBP1 und PPRAG protein expression in the SLC-KO mice occurred in the pericentral zone which is in line with published data from mice fed with a high fat diet ( Inoue et al, 2005 ; Liu, 2012 ). For SREBP1 it was shown that this protein has binding sites at -7000 bp and -500 bp of the Fasn gene ( Amemiya-Kudo et al, 2002 ; Morishita et al, 2014 ). Furthermore it was also shown that overexpression of SREBP1c, an isoform of SREBP1, lead to significant upregulation of Fasn gene expression in hepatocytes ( Dentin et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The novel epigenetic model regulates the efficacy of mRNA synthesis, for example from 100% to 140%. Recently, our study demonstrated that high carbohydrate intake enhances histone acetylation in the gene body rather than in the promoter/enhancer region of carbohydrate-responsive genes, such as carbohydrate digestion-and absorption-related genes including sucraseisomaltase, Sglt1, and Glut5 in the small intestine (Honma et al 2013, Inoue et al 2011, and Fas in the liver during the suckling-weaning transition period of rats (Morishita et al 2014). Carbohydrate-inducible fat accumulation-related genes in the liver, such as Cyp8b1, Dak, and Plin5, are similarly regulated by BRD4 (Yamada et al 2016).…”
Section: General and Novel Epigeneticsmentioning
confidence: 87%
“…For example, expression of glycerol‐3‐phosphate acyltransferase‐1, a fatty acid synthesis‐related gene, in the liver increased and DNA methylation of the gene decreased during periods of changing diets from milk (a high fat diet) to solid food (a high carbohydrate diet) in the process of weaning mice (Ehara et al ). In addition, we have demonstrated that expression of fatty acid synthase ( Fas ) in the liver and histone acetylation of the gene increased during the suckling‐weaning transient period (Morishita et al ). It was reported that unsaturated fatty acids, which are found in milk, enhanced genes related to fatty acid oxidation by demethylating DNA in the promoter/enhancer region of genes (Ehara et al ).…”
Section: Epigenetic Evidence Of the Dohad Theory In Animal Modelsmentioning
confidence: 99%
“…This is subsequently bound by positive elongation factor b (P-TEFb), which is a cyclin T1-CDK9 complex. BRD4 and the associated P-TEFb complex on the gene body region enhance transcriptional elongation by phosphorylating RNA polymerase II at the second serine residue of the C-terminal domain [12][13][14] (Figure 5B). …”
Section: Epigenetic Responses To Environmental Factorsmentioning
confidence: 99%
“…The epigenetic model of gene regulation based on histone modifications and DNA methylation in the gene body region explains the efficacy of mRNA synthesis. Our recent studies in rats have demonstrated that carbohydrate intake increases histone acetylation in the gene body region, rather than in the promoter/enhancer region, of carbohydrate metabolism-related genes, such as sucrose-isomaltase, sodium glucose transporter 1, and glucose transporter 5 in the small intestine [12,13], and fatty acid synthase in the liver during the suckling-weaning transition period [14]. In addition, we have demonstrated that fructose-inducible genes related to fat accumulation, such as Cyp8b1, Dak, and Plin5, are regulated by BRD4 in the liver [15].…”
Section: Epigenetic Responses To Environmental Factorsmentioning
confidence: 99%